2012
DOI: 10.3329/cardio.v4i2.10459
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Hemodialysis Patients

Abstract: Abstract:Background: Pulmonary hypertension (PH) has been reported to be high among maintenance dialysis patients. There is a paucity of data on the incidence and prevalence of pulmonary hypertension in chronic kidney disease (CKD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…[18] found PH prevalence to be as low as 26.74% and Moniruzzaman et al . [5] found it to be as high as 68.6%. In another Indian study Patel et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[18] found PH prevalence to be as low as 26.74% and Moniruzzaman et al . [5] found it to be as high as 68.6%. In another Indian study Patel et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PH in this cohort was 41% and the highest prevalence was in the HD group (33%). The variability in the prevalence of PH among CKD patients in different studies[518192021] can be explained by the difference in the ethnicity of the population studied as well as in the study group, regarding stage of CKD, mode of dialysis (HD vs PD), comorbid conditions such as COPD/CHF and inclusion criteria. Though these studies considered different parameters and are not truly comparable, most concluded that there was high prevalence of PH among CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations